What Is Implicit? - Gert Helgesson (Crítica)
This paper briefly surveys previous analyses of implicitness and proposes a new, two-dimensional account. The first dimension concerns whether an assumption follows or not in terms of analytical or contextual implications or because it is a reasonable interpretation. The second dimension concerns the intentions of the author. Both dimensions are needed for identifying implicit assumptions in critical analyses of texts. A definition of clear cases of implicit assumptions is given.